Test-retest reliability of the N2 event-related potential in school-aged children with autism spectrum disorder (ASD). Issue 2 (February 2020) - Cremone-Caira, Amanda; Vaidyanathan, Akshita; Hyatt, Danielle; Gilbert, Rachel; Clarkson, Tessa; Faja, Susan
Highlights: The N2 ERP component is commonly used as a biomeasure in children with autism. The test-retest reliability of N2 has not been explored in this population. Here, we report moderate to good retest reliability of N2 amplitude in children with autism. Abstract: Objective: The N2 ERP component is used as a biomeasure of executive function in children with autism spectrum disorder (ASD). The aim of the current study was to evaluate the test-retest reliability of N2 amplitude in this population. Methods: ERPs were recorded from 7 to 11-year-old children with ASD during Flanker ( n = 21) and Go/Nogo tasks ( n = 14) administered at two time points separated by approximately three months. Reliability of the N2 component was examined using intraclass correlation coefficients (ICCs). Results: Reliability for mean N2 amplitude obtained during the Flanker task was moderate (congruent: ICC = 0.542, 95% CI [0.173, 0.782]; incongruent: ICC = 0.629, 95% CI [0.276, 0.831]). Similarly, reliability for the Go/Nogo task ranged from moderate to good ('go': ICC = 0.817, 95% CI [0.535, 0.937]; 'nogo': ICC = 0.578, 95% CI [0.075, 0.843]). Conclusions: These findings support the use of N2 amplitude as a biomeasure of executive function in school-aged children with ASD. Significance: This research addresses a critical gap in clinical neurophysiology, as an understanding of the stability and reliability of the N2 component is needed in order to differentiate variance explained by repeated measurement versus targeted treatments and interventions.